Constitutive models for the thermo-mechanical and dynamic behavior of high-density polyethylene - A. Alhourani; I. Barsoum; S. Deveci; J. Sheikh-Ahmad; A. Abdelgawad (Polymer Testing, 2025)
Understanding the temperature and rate-dependent behavior of high-density polyethylene (HDPE) is crucial for the long-term integrity of various applications, particularly for the design of subsea HDPE pipelines against accidental loads. Consequently, recognizing HDPE's sensitivity to time and temperature necessitates the development of robust and complex constitutive and damage models. This study considers and calibrates three constitutive models for HDPE, including the Three Network (TN), the Three Network Viscoplastic (TNV) and the Johnson-Cook model (JC). The calibration carried out was based on tensile tests at various strain rates and elevated temperatures, and validated against drop weight impact tests at multiple speeds. The numerical results demonstrate that the TN model is superior in predicting the mechanical response and damage behavior of HDPE, in comparison with the JC and TNV constitutive and damage models. It shows markedly good agreement between experimental impact tests and numerical predictions across all impact scenarios. These findings demonstrate the accuracy and reliability of the TN material model for designing and assessing the response of HDPE components subjected to low-velocity impact. The study also verifies the effectiveness of the calibrated model in predicting damage behavior and determining the perforation limit of subsea HDPE pipelines under structural impact loads.